2002
DOI: 10.1037/0735-7028.33.6.557
|View full text |Cite
|
Sign up to set email alerts
|

Child custody cases: A content analysis of evaluations in practice.

Abstract: Guidelines for custody evaluations recommend multiple ways for assessing the parent-child relationship and outline appropriate means of assessing special issues such as domestic violence, child abuse, and substance use. However, little is known about the implementation of these guidelines in practice. This study examines 60% of custody evaluations in one circuit court over a 2-year period. Custody evaluations were examined for adherence to guidelines and for differences based on evaluator training. This analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 24 publications
0
37
0
1
Order By: Relevance
“…One of Bow's surveys examined the quality of custody reports (Bow & Quinnell, 2002) and another surveyed the concerns of lawyers and judges about custody evaluations and evaluators (Bow & Quinnell, 2004). Another study, using a small sample of convenience, studied the forensic quality of the reports and evaluations (Horvath, Logan, & Walker, 2002). Kelly and Ramsey (2008) recently called for research on the effectiveness of custody evaluations or a cost=benefit analysis of what evaluations really provide in light of their use of court and financial resources.…”
Section: Role Of the Reviewer In Child Custody Casesmentioning
confidence: 98%
“…One of Bow's surveys examined the quality of custody reports (Bow & Quinnell, 2002) and another surveyed the concerns of lawyers and judges about custody evaluations and evaluators (Bow & Quinnell, 2004). Another study, using a small sample of convenience, studied the forensic quality of the reports and evaluations (Horvath, Logan, & Walker, 2002). Kelly and Ramsey (2008) recently called for research on the effectiveness of custody evaluations or a cost=benefit analysis of what evaluations really provide in light of their use of court and financial resources.…”
Section: Role Of the Reviewer In Child Custody Casesmentioning
confidence: 98%
“…Finally, half of the reports indicated that a parent-child observation had occurred, but did not provide any information about the observation. Horvath, Logan, and Walker (2002) also conducted an analysis of child custody reports, reviewing 82 cases. However, the sample only involved cases from one Circuit Court in a Midwestern state, which represented a middle-class, urban, mostly Caucasian population.…”
Section: Journal Of Child Custodymentioning
confidence: 99%
“…These professionals have seriously questioned the adequacy of research 24 JOURNAL OF CHILD CUSTODY supporting child custody determinations, the role of the evaluator, and the appropriateness of addressing the ultimate issue. The present article reviews the empirical research concerning child custody practice, including the following studies: Ackerman and Ackerman (1997); Ackerman, Ackerman, Steffen, and Kelley-Poulos (2004); Bow and Quinnell (2001, 2004; Bow, Quinnell, Zaroff, and Assemany (2002); Bow and Boxer (2003); Gourley and Stolberg (2000); Horvath, Logan, and Walker (2002); Keilin and Bloom (1986); LaFortune (1997); LaFortune and Carpenter (1998); and Quinnell and Bow (2001).…”
mentioning
confidence: 99%
“…Gould et al (2007) report these findings as if they reflected actual practice; a number of studies suggest otherwise. Research in Kentucky found domestic violence was not only overlooked by evaluators as a general rule, but that it played no role in recommendations even when it was mentioned in their reports (Horvath, Logan, & Walker, 2002). Moreover, studies in both Kentucky and California found that domestic violence couples were as likely as those without such allegations to be steered into mediation and that mediators held joint sessions in nearly half of the cases where domestic violence was substantiated in an independent interview, even though this was against the regulations (Hirst, 2002).…”
Section: The Response To Abuse By the Family Courtmentioning
confidence: 99%